# 2x+2(-7x+3)=5x+2(3x-5)+5

## Simple and best practice solution for 2x+2(-7x+3)=5x+2(3x-5)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2x+2(-7x+3)=5x+2(3x-5)+5 equation:

2x+2(-7x+3)=5x+2(3x-5)+5
We move all terms to the left:
2x+2(-7x+3)-(5x+2(3x-5)+5)=0
We multiply parentheses
2x-14x-(5x+2(3x-5)+5)+6=0

We calculate terms in parentheses: -(5x+2(3x-5)+5), so:
5x+2(3x-5)+5
We multiply parentheses
5x+6x-10+5
We add all the numbers together, and all the variables
11x-5
Back to the equation:
-(11x-5)

We add all the numbers together, and all the variables
-12x-(11x-5)+6=0
We get rid of parentheses
-12x-11x+5+6=0
We add all the numbers together, and all the variables
-23x+11=0
We move all terms containing x to the left, all other terms to the right
-23x=-11
x=-11/-23
x=11/23

`